Differential genotypes of TNF-α and IL-10 for immunological diagnosis in discoid lupus erythematosus and oral lichen planus: A narrative review - Wang, Ruochong; Zhang, Xuefeng; Wang, Siyu (Frontiers in Immunology, 2022)
Discoid lupus erythematosus and oral lichen planus are chronic systemic immune system-mediated diseases with unclear etiology and pathogenesis. The oral mucosa is the common primary site of pathogenesis in both, whereby innate and adaptive immunity and inflammation play crucial roles. The clinical manifestations of discoid lupus erythematosus on the oral mucosa are very similar to those of oral lichen planus; therefore, its oral lesion is classified under oral lichenoid lesions. In practice, the differential diagnosis of discoid lupus erythematosus and oral lichen planus has always relied on the clinical manifestations, with histopathological examination as an auxiliary diagnostic tool. However, the close resemblance of the clinical manifestations and histopathology proves challenging for accurate differential diagnosis and further treatment. In most cases, dentists and pathologists fail to distinguish between the conditions during the early stages of the lesions. It should be noted that both are considered to be precancerous conditions, highlighting the significance of early diagnosis and treatment. In the context of unknown etiology and pathogenesis, we suggest a serological and genetic diagnostic method based on TNF-α and IL-10. These are the two most common cytokines produced by the innate and adaptive immune systems and they play a fundamental role in maintaining immune homeostasis and modulating inflammation. The prominent variability in their expression levels and gene polymorphism typing in different lesions compensates for the low specificity of current conventional diagnostic protocols. This new diagnostic scheme, starting from the immunity and inflammation of the oral mucosa, enables simultaneous comparison of discoid lupus erythematosus and oral lichen planus. With relevant supportive evidence, this information can enhance physicians’ understanding of the two diseases, contribute to precision medicine, and aid in prevention of precancerous conditions.